THE EFFECT OF CHARACTER DEVELOPMENT, DISCIPLINE, AND MOTIVATION ON WORSHIP BEHAVIOR OF CADETS NAUTICAL POLYTCHNIC OF BAROMBONG MAKASSAR SOUTH SULAWESI - Syafril Sunusi, Muhammad; Kasim, Amrah; Sulaiman, Umar; Syamsuddin, Syamsuddin (International Journal of Social Science, 2025)
The type of research is a survey. The location is at the Barombong Maritime Polytechnic campus, Makassar, South Sulawesi. The population is 204 people. A sample of 51 people was drawn using a purposive random sampling technique. Data collection techniques: questionnaires, interviews, and documentation. Data analysis techniques: frequency tables, simple linear regression, and multiple regression. Conclusions of the study: (1) character building, worship discipline, worship motivation, and worship behavior in cadets of the Barombong Maritime Polytechnic, Makassar, South Sulawesi are categorized as moderate or need to be improved in worship activities as a Muslim, (2) character building, worship discipline, and worship motivation have a good effect both individually and together on worship behavior in cadets of the Barombong Maritime Polytechnic, Makassar, South Sulawesi. Character building, discipline, and motivation in worship according to Islamic teachings help cadets to behave positively and avoid negative behavior. Cadets will realize that committing sins will bring bad consequences, both in the world and in the hereafter. This can motivate cadets to avoid behavior that is detrimental to themselves and others. One of the efforts to improve character building, discipline, and motivation of cadets, Barombong Maritime Polytechnic has formed a character building center for cadets and students in the form of a permanent daily command (PHST) for cadets. Implications of the study: (1) factors of character building, worship discipline, and worship motivation were found to influence the worship behavior of Barombong Maritime Polytechnic cadets. Therefore, it is necessary to get attention from leaders, lecturers, instructors, and cadet mentors so that the worship behavior of cadets can be further improved, (2) participation of parents and families is very necessary, especially when cadets are on cruises so that they continue to pay attention to worship behavior when at home, and (3) the factors studied in this study are still limited. Therefore, it is necessary to continue to study other factors that are different from this study.